Lo ius soli: Storia, evoluzione e nuove prospettive nelle legislazioni moderne - Volpe, Marcelo (Vergentis, 2020)
The institute of ius soli, the criterion for the acquisition of citizenship, according to which one becomes a citizen because is born on the territory of a sovereign state internationally recognized, regardless of the citizenship of the parents, despite its ancient origins has always been at the center of great debates and continuous legislative interventions because this institute generates great divisions between those who intend it as a battle of civilization and who believes that it is exclusively a danger that contributes to the loss of any national identity of a people. The examination of the ius soli passes through ancient and modern state regulations, as well as magisterial documents and canonical laws, aimed, above all, to offer serious reflection on current issues, sensitizing the legislator, and jurists in general, to act to guarantee migrants and refugees the dignity of human beings.